182k views
4 votes
Solve for x and write your answer in simplest form: -(6/5x + 6) + 2 = -4/5(-5x + 7)

User Abhitalks
by
4.8k points

2 Answers

5 votes

Answer:

all work is shown and pictured

Solve for x and write your answer in simplest form: -(6/5x + 6) + 2 = -4/5(-5x + 7)-example-1
User Afewcc
by
5.5k points
6 votes

For this case we must find the value of x of the following equation:


- (\frac {6} {5} x + 6) +2 = - \frac {4} {5} (- 5x + 7)

We eliminate the parentheses taking into account that:


- * + = -\\- * - = +\\- \frac {6} {5} x-6 + 2 = 4x- \frac {28} {5}

We simplify the left side:


- \frac {6} {5} x-4 = 4x- \frac {28} {5}

Add
\frac {28} {5}to both sides:


- \frac {6} {5} x-4 + \frac {28} {5} = 4x

Add
\frac {6} {5} x to both sides:


-4+ \frac {28} {5} = 4x + \frac {6} {5} x\\\frac {-20 + 28} {5} =\frac {20x + 6x} {5}\\8 = 26x\\x = \frac {8} {26}\\x = \frac {4} {13}

Answer:


x = \frac {4} {13}

User Mike Cluck
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.